Quantification of Motility in Bacillus subtilis at Temperatures Up to 84°C Using a Submersible Volumetric Microscope and Automated Tracking - Dubay, Megan M.; Johnston, Nikki; Wronkiewicz, Mark; Lee, Jake; Lindensmith, Christian A.; Nadeau, Jay L. (Frontiers in Microbiology, 2022)
We describe a system for high-temperature investigations of bacterial motility using a digital holographic microscope completely submerged in heated water. Temperatures above 90 ºC could be achieved, with a constant 5 ºC offset between the sample temperature and the surrounding water bath. Using this system, we observed active motility in Bacillus subtilis up to 66 ºC. As temperatures rose, most cells became immobilized on the surface, but a fraction of cells remained highly motile at distances of > 100 µm above the surface. Suspended non-motile cells showed Brownian motion that scaled consistently with temperature and viscosity. A novel open-source automated tracking package was used to obtain 2D tracks of motile cells and quantify motility parameters, showing that swimming speed increased with temperature until ~40 ºC, then plateaued. These findings are consistent with the observed heterogeneity of B. subtilis populations, and represent the highest reported temperature for swimming in this species. This technique is a simple, low-cost method for quantifying motility at high temperatures and could be useful for investigation of many different cell types, including thermophilic archaea.